Blockchain ​​and Smart Contract Applications Can Be A Support For Msme Supply Chain ​​finance Based On Sharia Crowdfunding - Ayu Sanjaya, Yulia Putri; Akhyar, Musthofa Ainal (Blockchain Frontier Technology, 2022)
Financial supply chain (Supply Chain Finance/SCF) is a hot topic in supply chain management research (Supply Chain Management). SCF's goal is to diversify funding sources from companies with limited capital and be able to improve financial efficiency throughout the company's supply chain network. SCF has become a source of short-term funding for thousands of micro, small and medium enterprises (MSMEs). The current research on SCF still uses a conventional financial framework, and no SCF research uses an Islamic financial framework. This study aims to develop an SCF framework and system based on Islamic sharia principles in the form of a sharia crowdfunding platform using blockchain technology and smart contracts. The system design produced by this research uses smart contracts that are run using the Ethereum protocol to prevent fraud/embezzlement and improve the security system on the planned platform, according to blockchain characteristics, which are very difficult to take over.